A CONFIRMATORY FACTOR ANALYSIS MODEL OF BENEFITS ARRANGEMENT GUIDELINES FOR ELDERLY WORKERS IN EASTERN THAILAND CONCERNING THE CONCEPTS OF SUFFICIENCY ECONOMY - Tanoamchard, wanvicechanee (RMUTT Global Business and Economics Review, 2019)
This research aimed to confirm a Model of Benefits Arrangement Guidelines for Elderly Workers in Eastern Thailand Concerning the Concepts of Sufficiency Economy with empirical data. The model was developed from previous qualitative research and tested by using a Confirmatory Factor Analysis (CFA). Data was collected through the structural closed-end questionnaires with 360 samples of elderly workers and executive managers in the eastern region of Thailand, and received 312 responses (86.66%). The results confirmed that the model consisting of 3 different approaches that were 1) preparing educations for retirement, 2) establishing welfare policies for the elderly, and 3) collaborating between companies and the aging workforce fit well with the empirical data (c2/df = 1.71, GFI = 0.95, AGIF = 0.92, RMSEA = 0.05, CFI = 0.99, NFI = 0.97). The standard weight of all indicators displayed in this model were found to be statistically significant (P<0.001). The component weight (b) and the ability to explain the components in each factor (R2) showed that providing information on the rights and welfare for the elderly workers (b = 0.94, R2 = 0.89), determination of other financial support policies (b = 0.82, R2 = 0.67), and sharing of sufficiency living experiences with others (b = 0.79, R2 = 0.62) had the highest component weight and the ability to explain components in each aspect by 89, 67 and 62 percent respectively. It could be concluded that the model of benefits arrangements guidelines for elderly workers in Eastern Thailand can be used to describe the benefits arrangements guidelines for elderly workers in Eastern Thailand and areas in the same context.